Identification of gallotannins and ellagitannins in aged wine spirits: A new perspective using alternative ageing technology and high-resolution mass spectrometry. (15th July 2022) - Fernandes, Tiago A.; Antunes, Alexandra M.M.; Caldeira, Ilda; Anjos, Ofélia; de Freitas, Victor; Fargeton, Laurent; Boissier, Benjamin; Catarino, Sofia; Canas, Sara
Graphical abstract: Highlights: Novel information on the influence of oxygen and chestnut wood on hydrolysable tannins. LC-ESI-HRMS/MS analysis of WS produced under distinct ageing technologies. Hydrolysable tannins formation/degradation pathways in WS ageing. Alternative technologies using micro-oxygenation for sustainable wine spirits' ageing. Abstract: This research was focused on identifying gallotannins and ellagitannins degradation pathways to better understand their behavior in complex media such as wine spirits (WS). A WS was aged with chestnut wood staves with three levels of micro-oxygenation, nitrogen, and using wooden barrels. Gallotannins and ellagitannins were identified by LC-ESI-HRMS/MS using a Q-TOF in samples collected at 8, 21, 60, 180, 270, and 365 days of ageing, allowed comparing their relative abundances according to the ageing technology. It was established for the first time, the importance of oxygen in gallotannins and ellagitannins formation/degradation pathways in WS and shading light into the explanation for the steady increase of gallic and ellagic acid contents on WS during ageing. The results also highlighted the presence of penta- O -galloyl-β-d -glucose, tetra- O -galloyl-β-d -glucose, tri- O -galloyl-β-d -glucose, di- O -galloyl-β-d -glucose, and mono- O -galloyl-β-d -glucose, 2, 3-(S)-hexahydroxydiphenoyl-β-d -glucose, pedunculagin, isomers vescalagin/castalagin and two products stemming from ethanol-promoted oxidation of castalagin/vescalagin and vescalin/castalin, in the composition WS aged with chestnut wood.